PENGARUH PENERAPAN MEDIA PEMBELAJARAN PPKN MENGGUNAKAN ANALOGI GAMELAN GONG KEBYAR TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 1 SAWAN - Komang Ayu Kanya Diva Gayatri; Kertih, I Wayan; Sidaryanti , Ni Nyoman Asri (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2025)
Abstract Implementing instructional media in the subject of Civic Education (PPKn) using the analogy of the Gong Kebyar gamelan on students’ learning outcomes. This research of innovation in instructional media, which has contributed to students’ low comprehension and interest in Civic Education. To address this issue, an educational video was developed that links the concept of Bhinneka Tunggal Ika (Unity in Diversity) with elements of Balinese local culture, particularly the Gong Kebyar gamelan, which symbolizes harmony in diversity. The study employed a quasi-experimental approach using a one-group pre-test–post-test design, with the research sample consisting of seventh-grade students from SMA Negeri 1 Sawan during the 2024/2025 academic year. The data analysis revealed a significant improvement in students’ learning outcomes following the implementation of the instructional media. These findings suggest that incorporating local cultural wisdom such as the Gong Kebyar gamelan into educational media can effectively enhance students’ understanding of Civic Education content and promote more active engagement in the learning process. Keywords: instructional media, Gong Kebyar gamelan, learning outcomes, civic education